2007
DOI: 10.2337/db06-1110
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of the Peroxisome Proliferator–Activated Receptor-α Gene (PPARA) Influence the Conversion From Impaired Glucose Tolerance to Type 2 Diabetes

Abstract: for the STOP-NIDDM Study Group* Peroxisome proliferator-activated receptor (PPAR) ␣, a transcription factor of the nuclear receptor superfamily, regulates fatty acid oxidation. We evaluated the association of single nucleotide polymorphisms (SNPs) of the PPAR-␣ gene (PPARA) with the conversion from impaired glucose tolerance to type 2 diabetes in 767 subjects of the STOP-NIDDM trial in order to investigate the effect of acarbose in comparison with placebo on the prevention of diabetes. In the placebo group, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…Regarding the regulatory mechanism of NPC1L1 expression, we demonstrated that, in addition to SREBP2, several transcriptional factors such as hepatocyte nuclear factor 4α (HNF4α/NR2A1), peroxisome proliferator-activated receptor α (PPARα/NR1C1), and PPARγ coactivator 1α (PGC1α) positively regulate the mRNA expression of NPC1L1. 15,49) Taken together with facts that both HNF4α and PPARα are involved in the pathogenesis of diabetes [50][51][52] and that intestinal expression of PGC1α is increased under diabetic conditions, 53) our findings indicate that these transcriptional factors may play important roles in the regulation of NPC1L1 expression under diabetic conditions and at least partly account for clinical associations between progressions of T2DM and other cholesterol-related diseases such as dyslipidemia and NAFLD/ NASH. 54,55) …”
Section: Npc1l1 and T2dmsupporting
confidence: 58%
“…Regarding the regulatory mechanism of NPC1L1 expression, we demonstrated that, in addition to SREBP2, several transcriptional factors such as hepatocyte nuclear factor 4α (HNF4α/NR2A1), peroxisome proliferator-activated receptor α (PPARα/NR1C1), and PPARγ coactivator 1α (PGC1α) positively regulate the mRNA expression of NPC1L1. 15,49) Taken together with facts that both HNF4α and PPARα are involved in the pathogenesis of diabetes [50][51][52] and that intestinal expression of PGC1α is increased under diabetic conditions, 53) our findings indicate that these transcriptional factors may play important roles in the regulation of NPC1L1 expression under diabetic conditions and at least partly account for clinical associations between progressions of T2DM and other cholesterol-related diseases such as dyslipidemia and NAFLD/ NASH. 54,55) …”
Section: Npc1l1 and T2dmsupporting
confidence: 58%
“…Additionally, PGC1α is suggested to have stimulatory effects on the SREBP2/HNF4α-and PPARα/RXRα-mediated transactivation of the human NPC1L1 promoter. Taken together with the involvement of HNF4α, PPARα and PGC1α in the pathogenesis of diabetes (20,21,27), these findings may provide new insights into the close relationship of glucose, fatty acids and cholesterol homeostasis.…”
Section: Resultsmentioning
confidence: 79%
“…6). Because HNF4α and PPARα are also involved in the pathogenesis of diabetes (20,21,27), it is possible that these factors play important roles in the regulation of NPC1L1 expression under (patho)physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical studies did not reveal any effect of PPARα ligands on glucose parameters in patients with T2DM, PPARα ligands have the intriguing potential to prevent the progression from prediabetes to T2DM as suggested by post hoc analysis of the Bezafi brate Infarction Protection (BIP) study [13]. Moreover, PPARα gene variations have been reported to associate with the onset of and progression to T2DM in humans [14,15].…”
Section: Metabolic Activities Of Pparα and Pparγmentioning
confidence: 99%